6ER-029 Impact of a medicines information app on medication knowledge and worry in post-myocardial infarction patients. (14th March 2021) - Campbell, G; Devaney, C; Auyeung, V; Ismail, TF; Weinman, J
Abstract : Background and importance: Non-adherence to medications post-myocardial infarction (MI) is well documented. This can lead to inappropriate therapeutic escalation and early mortality. Identifying effective interventions to support patients with the management of medications is therefore of paramount importance. Aim and objectives: MedTap is a medicines information app developed by clinicians for patients and carers. The objective of this study was to evaluate whether utilising MedTap had any impact on patient knowledge and worry. Material and methods: Patients admitted to a cardiology ward at a tertiary hospital with an MI completed a baseline questionnaire to assess medication knowledge and worry before discharge. They were given access to medicine information via MedTap. A post-use questionnaire was completed via telephone 2 weeks later. The questionnaire was developed utilising existing validated adherence questions. Questions were grouped into 'knowledge' (n=5) and 'worry' (n=3) for analysis. A score of 1 was assigned to yes responses and a score of 0 for no, and change over time was assessed with a paired Wilcoxon test. Results: 54 patients were recruited (mean age 63 years, 4 women), with 10 (18.5%) lost to follow-up. Of the 44 patients interviewed, 22 (50%) used the app. For users, the median pre-knowledge score was 3 (range 1–5) with a median change of 1 (range −1 to 4). There was a significant increase in knowledge (p=0.003) at the 2 week follow-up. For users, the median pre-worry score was 0 (range 0–2) with a median change of 0 (range −2 to 0). However, this still translated into a net reduction in worry (p=0.011). For non-users, the median pre-knowledge score was 3 (range 0–5) with a median change of 1.5 (range −4 to 4). There was an increase in knowledge (p=0.009) at follow up. For non-users, the median worry score was 0 (range 0–2) with a median change of 0 (range −1 to 2). There was no significant change in worry (p=0.739). Conclusion and relevance: This study has shown that a digital app can be used as an additional tool to deliver medicines information, improve patient knowledge and decrease patient medication worry. A reduction in worry is significant as this is known to significantly influence adherence behaviour. Further work will assess adherence and determine whether using MedTap has an impact on clinical outcomes. References and/or acknowledgements: Conflict of interest: No conflict of interest